FC 070USE OF POTENTIALLY NEPHROTOXIC MEDICATIONS IN PERSONS WITH CHRONIC KIDNEY DISEASE: PARALLEL COHORT STUDIES IN SWEDISH AND U.S ROUTINE CARE. (29th May 2021) - Bosi, Alessandro; Carrero, Juan Jesus; Shin, Jung-Im; Xu, Yunwen; Grams, Morgan; Chang, Alexander; Wettermark, Bjorn; Barany, Franz Peter; Gasparini, Alessandro
Abstract: Background and Aims: Many adverse drug events are preventable, such as those potentially resulting from the prescription of nephrotoxic drugs to persons with chronic kidney disease (CKD). We here quantify the extent of contemporary nephrotoxic medication use in patients with CKD. Method: In two observational cohorts of Swedish (Stockholm CREAtinine Measurements [SCREAM] project, Stockholm, Sweden) and U.S. (Geisinger Health System, Pennsylvania) adults with confirmed CKD stages G3-G5 undergoing routine care during 2016-2018, we explored the prescription (in U.S.) and dispensation (in Sweden) of 115 different ambulatory drugs with proven or purported nephrotoxicity during the 12 months following study inclusion. We evaluated the proportion of participants receiving nephrotoxic drugs, ranked main contributors and identified clinical predictors. Results: In the Swedish cohort, there were 57880 patients (54.6% women) with median age of 80.00 (inter-quartile range [IQR]: 73.0-86.0) years and eGFR 48.9 ([IQR]: 39.9-55.0) mL/min/1.73 m 2 . In the U.S. cohort, there were 16255 patients (59% women) with median age of 76 years and eGFR 44 mL/min/1.73 m 2 . During observation, 20% (Sweden) and 17% (U.S.) of patients received at least one nephrotoxic drug. The top 3 potentially inappropriate nephrotoxic drugs identified were NSAIDs (9% and 11% of participants in U.S. and Sweden received it), antivirals (2.0% and 2.5%) and immunosuppressants (1.5% and 2.7%). Bisphosphonate use was common in Sweden (3.3% of participants), but not in U.S. (0.5%). Conversely, fenofibrates were common in U.S. (3.6%), but not in Sweden (0.13%). In adjusted analyses, patients with young age (<65 years old), women, or with CKD G3 were at higher risk of receiving nephrotoxic medications in both cohorts (P>0.05 for all). Notably, patients aware of their CKD (identified either by issued diagnosis or recent visit to a nephrologist), were at lower risk of nephrotoxic drug use (OR 0.87, 95% CI 0.82-0.92 in Sweden and 0.89, 95% CI 0.81-1.01 in U.S.). Conclusion: In two geographically distinct health systems, one in five patients with CKD received potentially inappropriate nephrotoxic medications, mainly NSAIDs. Strategies to increase CKD awareness and physician's knowledge of drug nephrotoxicity may reduce inappropriate ambulatory prescriptions and prevent iatrogenic kidney injury.